The Lutetian Society - Merkle, Denise (TTR, 2003)
AbstractThis paper will examine the role of the late-Victorian Lutetian Society translators (Alexander Teixeira de Mattos, their leader, Ernest Dowson, Havelock Ellis, Percy Pinkerton, Victor Plarr, Arthur Symons) as translating subjects and cultural agents, united by the “cause” of providing British readers with unexpurgated translations of some of Émile Zola’s maligned, if not banned, masterpieces so that they might be able to form an unbiased opinion of the literary merits of the works. Furthermore, the paper will explore what motivated these translators to join in this clandestine translation project and try to give some insight into the effect of their (re)translation activity on their personal appreciation of Zola and the novel translated. The paper concludes that the act of (re)translation served to expand the cultural horizons of the Lutetian Society translators. Their translations would, in turn, expand the cultural horizons of those who read them.